Comparison of gadobutrol and meglumine gadoterate for dynamic contrast-enhanced MRI of pituitary macroadenomas - Kihwan Hwang; Yun Jung Bae; Chae-Yong Kim; Da Hyun Lee; So Yeong Jeong; Se Jin Cho; Sung Hyun Baik; Leonard Sunwoo; Byung Se Choi; Cheolkyu Jung; Jae Hyoung Kim (Scientific Reports)
Abstract In this study, we compared the performance of gadobutrol and meglumine gadoterate, two macrocyclic non-ionic and ionic contrast agents, for evaluating quantitative perfusion parameters of pituitary macroadenomas using dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI). Patients with pituitary macroadenomas were prospectively enrolled and randomly assigned to be administered gadobutrol or meglumine gadoterate for MRI. Perfusion parameters of the pituitary macroadenoma, including Ktrans, Kep, Ve, and Vp, were measured using DCE-MRI. In total, 60 patients (mean age: 59.7 ± 13.7 years; 40 men) were evaluated. The non-inferiority test confirmed that gadobutrol was comparable to meglumine gadoterate for measuring the Ktrans of the pituitary macroadenoma. Kep was significantly higher with gadobutrol (P = 0.001) irrespective of tumor functional status and aggressiveness. Ktrans, Ve, and Vp and pre- and post-contrast T1-signal intensities of the tumor did not differ significantly for contrast agents. Perfusion parameters were not significantly associated with diagnostic performance in distinguishing the tumor functional status (P > 0.05). In summary, gadobutrol is non-inferior to meglumine gadoterate for the Ktrans measurement of pituitary macroadenomas. However, gadobutrol may lead to higher Kep, regardless of tumor functional status and aggressiveness. Awareness of this variation is crucial to preventing misinterpretation of vascular dynamics in pituitary macroadenomas.